CEO Incentives and Firm Size - Baker, George P.; Hall, Brian J. (Journal of Labor Economics, 2004)
We develop a model that clarifies how to measure CEO incentive strength and how to reconcile the enormous differences in pay sensitivities between executives in large and small firms. The crucial parameter is shown to be the elasticity of CEO productivity with respect to firm size. We find that CEO marginal products rise significantly with firm size (confirming Rosen's conjecture that CEOs of large firms have a "chain letter" effect on firm performance), and overall CEO incentives are roughly constant, or decline slightly, with firm size. We employ a multitask model to discuss implications for the design of control systems.